The Labor Supply Effects of Welfare Reform - Timothy J. Bartik (W.E. Upjohn Institute for Employment Research, 1998)
Will welfare reform increase unemployment and reduce wages? The answer depends in part on how much welfare reform increases labor supply. This paper considers the labor supply effects of the welfare reforms that have occurred since 1993, when President Clinton entered office with a promise to "end welfare as we know it." The paper reviews previous estimates, and provides new estimates, of how many additional labor force participants have entered the labor force due to welfare reform. I estimate that welfare reform from 1993-96 increased the U.S. labor force by between 100,000 and 300,000 persons. Between 1996, when the major federal welfare reform bill was enacted, and 1998, welfare reform has probably increased the U.S. labor force by at least another 300,000 persons. Assuming current policy trends continue, welfare reform may add another half-million to one-million labor force participants between 1998 and 2005. The cumulative impact of welfare reform from 1993-2005 is likely to add between one and one-and-a-half million persons to the U.S. labor force. This additional labor supply is not huge compared to the U.S. labor force, so welfare reform is unlikely to have large long-run effects on overall wages and unemployment. However, this additional labor supply is large compared to likely growth in labor demand for less-educated women over the 1993-2005 period. As a result, welfare reform is likely to have significant effects on the wages and unemployment rates of less-educated women during the 1993-2005 period.
Keywords: J0; J1; J6; 330; welfare; reform; labor; supply; Bartik